KASTA DAN WARNA: SEBUAH KRITIK DALAM MASYARAKAT EGALITER - Sudarsini, Ni Nengah (PANGKAJA: JURNAL AGAMA HINDU, 2018)
The caste system is one of the foundations of the emergence of social problems in society. Indeed caste is one of the tactics of colonists in the Dutch colonial period that tried to influence and divide the unity and unity of Balinese society, making it easy to conquer. Actually known as Catur Warna, the goal is not to distinguish one group from another vertically, but because of the procession and ability of each individual. Here it is clear that warna is the name for people who master a particular field. If the society is not organized by warna, then there will be problems arising in social life. From this concept it is important to emphasize that everyone has the right to increase his or her dignity to be superior to others. All of warna have the opportunity to develop goodness for the sake of lofty ideals, this is the real principle of equality or egalitarianism. In a spiritual perspective, the real hu- man existence is the identification or recognition of the self with the atma that in Hinduism involves the principle of yoga that God is in every human being, therefore, the principle of Godhead in every being is the same. This means that God is in all beings so that there is unity in all of His creations.